ANALISIS KEBIJAKAN KEPALA SEKOLAH DI SD DALAM PEMBELAJARAN DI MASA PANDEMI COVID 19 - Annisa Maharani, Riqqah; Maulani, Yulia; Kharisna, Feby (Study program PGSD FKIP Universitas Bung Hatta, 2022)
This study aims to determine the principal's policy in carrying out bold learning for students during the Covid 19 pandemic in the hope that students will get an effective and conducive education. The research method used is descriptive qualitative method. Data analysis interactive model of data collection, data reduction, data presentation, and drawing conclusions. With data sources principals, teachers, parents and students. Data collection techniques are observation, interviews and documentation. The results of this study indicate that the local SDN principal already has a policy in implementing face-to-face learning through a number of students in accordance with the health protocol. Principals, teachers, homeroom teachers, parents and guardians of students as well as the local community participated in the success of the policy.